Verbal Clauses in the Short Story of Al-Hilm Ar-Ra’i by Najeeb Al-Kailani (A Syntax Analysis) - Fadhilah, Zuhra Nur; Yoyo, Yoyo; Mukhlis, Abdul; Zaini, Abdul Razif; Ferawati, Ferawati (UIN Mahmud Yunus Batusangkar, Indonesia, 2025)
This paper tries to analyze verbal clauses in the short story Al-Hilm Ar- -Ra’i by Najeeb Al-Kailani by paying attention to the types and functions within the text. This research employs a descriptive qualitative approach using library research and short story analysis methods. The syntactic approach is used in this study. The focus of this research is the analysis of verbal clauses in the short story Al-Hilm Ar- Ra’i by Najeeb Al-Kailani as primary data. Secondary data were obtained from books and scientific articles using the syntactic analysis theory by Musthafa Al-Ghulayaini. The data collected consists of verbal clauses or jumlah fi’liyyah. The data collection technique used is the library research technique. Data analysis techniques include four parts: identifying the data, determining the data, and examining the data results. The results of the study show two types and positions of clauses. First, clauses that occupy a function in the sentence structure; within the short story, there were 9 verbal clauses (from all 27 data) that occupy a function in the sentences. Second, clauses that do not occupy a function in the sentence structure are indicated by 18 data. However, based on their positions, clauses can be divided into two categories: complete clauses and incomplete clauses. There were 9 complete clauses, and 7 incomplete clauses found. This research provides an in-depth understanding of verbal clauses and their various types and positions, as well as their relevance to theories in syntactic analysis. The implications of these findings can be used to help readers or other researchers expand their knowledge of Arabic language structure and possibly apply it in different contexts.